Amelioration of obesity-related metabolic disorders via supplementation of Caulerpa lentillifera in rats fed with a high-fat and high-cholesterol diet - Manoppo, Jeanette Irene Christiene; Nurkolis, Fahrul; Pramono, Adriyan; Ardiaria, Martha; Murbawani, Etisa Adi; Yusuf, Muhammad; Qhabibi, Faqrizal Ria; Yusuf, Vincentius Mario; Amar, Nasim; Karim, Muhammad Rico Abdul; Subali, Anita Dominique; Natanael, Hans; et al. (Frontiers in Nutrition, 2022)
Dietary modification, including functional foods, could reduce comorbidities due to obesity. An increase in serum glucose and lipids is often seen in obesity. Furthermore, obesity is also characterized by a decrease in antioxidant capacity (i.e. decrease of superoxide dismutase/SOD) and downregulation of peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α). It has been well established that PGC-1α is important to regulate mitochondria biogenesis. Sea grapes (Caulerpa lentillifera) are known as a traditional food in many Asia Pacific countries. Recent evidence suggests that sea grapes have many beneficial properties as functional foods and may have potential therapeutic functions. We investigated the effect of sea grapes (Caulerpa lentillifera) on serum glucose, lipids, PGC-1α, and protein levels of SOD in the liver of Rattus norvegicus which is induced with a high-fat and cholesterol diet. A total of four groups were made, each containing ten male Rattus norvegicus; group A received a standard dry pellet diet as control, group B received cholesterol- and fat-enriched diets (CFED), groups C and D received CFED and 150 and 450 mg/kg body weight (BW) of sea grapes extract respectively for four weeks. Serum glucose and cholesterol were assessed using blood auto-analyzer. Serum PGC-1α was measured using ELISA. SOD levels were calculated using the superoxide dismutase assay kit Sigma-Aldrich with blood taken from liver tissue. In this study, sea grapes extract improved total cholesterol level better than the CFED and normal groups. The efficacy of total cholesterol improvement was similar between the two doses of sea grapes extract. Furthermore, sea grapes extract increased PCG-1α levels, especially with the dose of 150 mg/kg BW. Blood glucose was also lower in the groups of sea grapes extract. Interestingly, the groups treated with sea grapes extract exhibited higher levels of liver SOD compared to normal and CFED groups. To conclude, sea grapes (Caulerpa lentillifera) have promising potential as anti-hyperglycemia, anti-hypercholesterolemia, and reduce oxidative stress, providing various health benefits for metabolic disorders.